2020
DOI: 10.3390/brainsci10040233
|View full text |Cite
|
Sign up to set email alerts
|

P-cresol Alters Brain Dopamine Metabolism and Exacerbates Autism-Like Behaviors in the BTBR Mouse

Abstract: Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social interaction/communication, stereotypic behaviors, restricted interests, and abnormal sensory-processing. Several studies have reported significantly elevated urinary and foecal levels of p-cresol in ASD children, an aromatic compound either of environmental origin or produced by specific gut bacterial strains. Methods: Since p-cresol is a known uremic toxin, able to negatively affect multiple brain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 67 publications
4
61
1
Order By: Relevance
“…C. difficile and Pseudomonas stutzeri are the main sources of p -cresol in humans [ 58 ]; this organic aromatic compound acts as a neuroactive uremic toxin and is increased in autistic subjects [ 59 ]. Our results confirm that the magnitude of the p -cresol increase was proportional to the severity of ASD core symptoms, as previously demonstrated in both humans and animal models [ 60 , 61 ], and is associated with slow bowel transit due to the decrease of gut motility [ 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…C. difficile and Pseudomonas stutzeri are the main sources of p -cresol in humans [ 58 ]; this organic aromatic compound acts as a neuroactive uremic toxin and is increased in autistic subjects [ 59 ]. Our results confirm that the magnitude of the p -cresol increase was proportional to the severity of ASD core symptoms, as previously demonstrated in both humans and animal models [ 60 , 61 ], and is associated with slow bowel transit due to the decrease of gut motility [ 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…p-Cresol (an alcohol) is produced from tyrosine [ 137 , 138 ] by 4-hydroxyphenylacetate decarboxylases [ 139 ]. It increases anxiety-like behaviors in mice [ 140 ], has cell toxicity [ 141 ] and acts as an insect attractant [ 142 ]. Moreover, 3-vinyl-1-cyclobutene is an unsaturated cyclic hydrocarbon found in the extract of Cornus officinalis (Japanese cornel), a traditional Chinese herbal medicine [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the causal relationship between social behavior and p-Cresol levels was not investigated. Also, a recent study showed that a single acute intravenous injection of p-Cresol exacerbated anxiety and reduced social preference in the BTBR idiopathic model of ASD 47 . Nonetheless, the intravenous administration of p-Cresol did not recapitulate chronic intestinal exposure and the broad observed effects may have resulted from acute activity of the compound.…”
Section: P-cresol Induces Asd Core Behavioral Deficitsmentioning
confidence: 98%